Rotina do Médico Veterinário à campo - Rodrigues, Keven Sterdanio Miranda Rodrigues (Universidade Federal do Tocantins, 2024)
This report presents in detail the experiences and learning acquired during the mandatory curricular internship required to obtain the title of veterinarian. The mandatory curricular internship lasted 390 hours and was carried out in a veterinary consultancy company, supervised by Veterinarian Givago Nascimento Arantes and under the guidance of Prof. Dr. Fabiana Cordeiro Rosa. During this period, activities included clinical care, pregnancy diagnoses, exams and reproduction. Highlighting greater relevance in Fixed-Time Artificial Insemination and surgeries associated with this practice, since this procedure was the most used in internship practice, bringing an understanding and application of reproductive biotechnologies to improve the productivity of beef cattle. The report also addressed the contributions of the internship to the development of clinical skills and the role of the veterinarian in promoting the well-being and health of animals, highlighting the importance of practical training in Veterinary Medicine.